تحليل المحتوى بين الكم والكيف - بن بوزيان, عبد الرحيم (جامعة الوادي - University of Eloued, 2022)
تعتبر تقنية تحليل المحتوى من أهم التقنيات المستخدمة لجمع وتحليل البيانات في بحوث اإلعالم واالتصال. وعلى ورغم من قِدم هذه التقنية وانتشار استخدامها في تخصصات علمية متنوعة، إال أنها مازلت تشهد تغييرات وتحوالت تسهم في تطويرها وجعلها أداة أكثر صحة وثبات ومالءمة لدراسة الظاهرة االتصالية. وقد هدفت هذه الورقة البحثية إلى مراجعة أسلوب تحليل المحتوى في ضوء المقاربات البحثية المهمينة في بحوث اإلعالم واالتصال وهي: المنهجية الكمية والكيفية والمناهج المختلطة. وتم التركيز على تقنية تحليل المحتوى المختلط كتقنية تجمع بين الجانبين الكمي والكيفي.Content analysis technique is one of the most important techniques used to collect and analyze data in media and communication research. Despite the age of this technique and its widespread use in various scientific disciplines, it still knows changes and transformations that contribute to its development and make it a more valid, reliable, and appropriate tool for studying the communication phenomenon. This paper aims to review the method of content analysis in light of the important research approaches in media and communication research, namely: quantitative and qualitative methodology and mixed methods approach. This paper focused too on the mixed methods content analysis technique as a technique that combines the quantitative and qualitative aspects.
Content Analysis between quantity and quality
مقال
Keywords: تحليل المحتوى، الكم، الكيف، تحليل المحتوى المختلط; Content Analysis, Quantity, Quality, Mixed methods content analysis.